POSTUR KERJA DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA MANUAL HANDLINGBAGIAN ROLLING MILL - Nurdian Evadarianto (Universitas Airlangga, 2017)
In the production process, a lot of activities that use human power, for example in material processing, packing and transportation of production manually. It if is not done the right way, it will lead to disruption in the system of muscles, bones, tendons, and nerves called with musculoskeletal disorders. This study was conducted to determine the relationship between work posture with the incidence of musculoskeletal disorders complaint. This research is an analytic observational with cross sectional approach, this study using a sample's total working population numbering 15 people. Techniques of collecting data through observation and questionnaires. For posture workers measured using valuation methods REBA, as well as the incidence of complaints of musculoskeletal disorders (MSDs) are measured by filling sheets of Nordic Body Map (NBM). Data were analyzed using Spearman correlation test. Results of this study was 73.34% working posture workers with very high category, 73.34% of workers complain of MSDs in the medium category. Spearman correlation coefficient value of 0.770, which means there is a very strong relationship between work posture with MSDs complaint. Ergonomic posture that does not work or is not natural occurrences can cause MSDs complaint. The worse the working posture, the greater the musculoskeletal complaints. Suggested improvements to the company to avoid layout with raised floor, doing routine surveillance on the activities that are at risk of bodily injury, and hold regular sports activities once a week.Keywords: Musculoskeletal Disorders, Work Posture